Immediate and One-Year Outcomes of an Asthma-Tailored Pulmonary Rehabilitation Programme in Overweight and Obese People with Difficult-to-Treat Asthma - Ricketts, Helen; Sharma, Varun; Steffensen, Femke; Mackay, Elaine; MacDonald, Gordon; Buchan, Duncan; Lean, Michael; Chaudhuri, Rekha; Cowan, Douglas (Journal of asthma and allergy, 2024)
Management of difficult-to-treat asthma is particularly challenging in people with elevated body mass index (BMI). Our randomised controlled trial of pulmonary rehabilitation (PR) showed improved outcomes at 8 weeks. Here we assess immediate and one-year effects of asthma-tailored PR in participants with difficult-to-treat asthma and BMI ≥25 kg/m , and identify response predictors. A prospective observational study of PR, tailored to asthma, comparing outcomes at baseline (V1), immediately after 8 weeks of PR (V2), and at 1 year (V3). Baseline characteristics were compared in responders/non-responders defined by achievement of minimum clinically important difference (MCID) for asthma control questionnaire (ACQ6) (0.5) at 8 weeks and 1 year. Of 92 participants, 56 attended V2 and 45 attended V3. Mean age was 60 (SD 13) years, 60% were female, and median (IQR) BMI was 33.8 (29.5-38.7) kg/m . At V1, V2, and V3, respectively, there were significant differences in ACQ6 (mean (95% CI): 2.5 (2.1-2.9), 2.2 (1.8-2.5), and 2.3 (1.9-2.7), <0.003), Borg breathlessness score post-6-minute walk test (median (IQR): 2 (0.5-3), 1 (0-2), and 1 (0.5-2), <0.035), and annualised exacerbations requiring prednisolone (median (IQR): 3 (2-5), 0 (0-4.7), and 1.5 (0-4.2), <0.003). A total of 27/56 (48%) had improvements >MCID for ACQ6 at V2 and 16 (33%) at V3. Participants with higher ACQ6 scores at baseline (suggesting poorer asthma control) were more likely to achieve MCID. Baseline BMI, within the range studied, was not predictive. Pulmonary rehabilitation induced improvements in asthma-related outcomes including perception of breathlessness, asthma control, and exacerbation frequency at 1 year. Those with poorer baseline asthma control were more likely to benefit.